STRENGTHENING SOCIAL PROTECTION FOR INDONESIAN MIGRANT WORKERS: ADDRESSING GAPS AND CHALLENGES IN THE NATIONAL SECURITY SYSTEM - Ismi Pratiwi Podungge; Nanik Prasetyoningsih (Masalah-Masalah Hukum, 2025)
Indonesian Migrant Workers (PMI) are citizens who work outside Indonesia, often facing significant legal and social challenges. One of the key issues is the lack of social security coverage, with 67.7% of migrant workers not enrolled in the BPJS Employment program. The Indonesian government’s Regulation of the Minister of Manpower No. 4 of 2023 aims to enhance social security for migrant workers by mandating their participation in BPJS Employment. However, various obstacles, such as overlapping regulations and workers’ preference for employer-provided insurance, persist. This study evaluates the alignment of this regulation with the principles of the National Social Security System (SJSN), focusing on its effectiveness in providing social protection to migrant workers. The analysis utilizes the theoretical frameworks of welfare state theory, social justice, and human rights to assess the extent to which the regulation fulfills its obligations. The findings show that while Permenaker No. 4 of 2023 offers more comprehensive benefits and extends protection from pre-placement to post-placement, it still faces issues such as inequitable contribution distribution and insufficient transparency. The research highlights that the regulation, although progressive, does not fully implement the principles of SJSN, particularly in terms of fairness and state responsibility. To achieve greater social justice, the study recommends strengthening regulatory mechanisms, ensuring fair contribution sharing, and improving information access and oversight. This research contributes to the understanding of the regulatory improvements needed to enhance the social security coverage for Indonesian migrant workers.